HUBUNGAN PERSEPSI SISWA TENTANG SUASANA LINGKUNGAN BELAJAR DIDALAM KELAS TEORI DENGAN HASIL BELAJAR RAB SISWA KELAS X1 SMK NEGERI 1 PADANG - 538-546 , Mikrizal (Universitas Negeri Padang, 2015)
Abstract This correlation reasearch are aims to find of relationship between students' perceptions about class environment and financial planning result of student XI class SMK Negeri 1 Padang. The population are students in XI class SMK Negeri 1 Padang students year 2013/2014 which is 97 students. The results showed that there is a relationship between students' perceptions about the atmosphere of the learning environment in the classroom theory with learning out comes financial planning training eye of class XI student of SMK Negeri 1 Padang. Mean an atmosphere of learning outcomes theoretical training eye financial planning class XI student of SMK Negeri 1 Padang. This can be seen from the degree of achievement of the respondents in the variable students’ perception about the atmosphere of the learning environment for students of class XI 70.06 %. While the learning outcomes Draft financial planning class XI Building Engineering Department SMK 1 Padang get enough value . This can be seen by the average level of achievement of learning outcomes at 74,96 . While the value ( r ) obtained for 0.630. Then diterminan coefficient obtained from the calculation of the contribution value of 39.69 %. Keywords: Perceptions, The Atmosphere of the Learning Environment and Learning outcomes